Determination of energy and protein requirements of growing guineafowl during cold season - Mandal, A B; Pathak, N N; Singh, Harpreet (The Indian Journal of Animal Sciences, 2012)
Unsexed guineafowls (397) of 3 varieties, viz. Pearl, White and Lavender, were fed 9 dietary treatments (3 energy x 3 protein levels) from 0 to 12 weeks of age in 3 growth phases (0-4, 4-8 and 8-12 weeks). Protein levels were Pâ‚, 24, 22, and 20; Pâ‚‚, 22, 20 and 18%, and Pâ‚ƒ, 20, 18 and 16% while energy concentrations in diet were Eâ‚, 12.13, 12.55 and 12.55; Eâ‚‚, 11.30, 11.72 and 11.72, and Eâ‚ƒ, 10.46, 10.88 and 10.88 MJ ME/kg for 0-4, 4-8 and 8-12 weeks of age, respectively. Live weight gain did not differ due to Eâ‚ or Eâ‚‚ levels up to 8 weeks, but during 8-12 weeks gain was higher (P<0.01) in Eâ‚ (12.55 MJ ME/kg) than Eâ‚‚ and Eâ‚ƒ.The difference in gain between Pâ‚ and Pâ‚‚ existed only up to 4 weeks and, thereafter remained similar due to Pâ‚ or Pâ‚‚ levels. Feed efficiency was always better in diet with energy concentration Eâ‚ while that on protein levels Pâ‚ and Pâ‚‚ remained similar at any age. It is concluded that the requirement of energy was 12.13 and 12.55 MJ ME/kg diet for 0-4 and 4-12 weeks with protein concentrations 24, 20 and 18%, for 0-4, 4-8 and 8-12 weeks of growth phases, respectively.